Drivers of caregiver impact in Duchenne muscular dystrophy: a cohort study. - Schwartz, Carolyn E.; Stark, Roland B.; Borowiec, Katrina.; Rapkin, Bruce D. (Tufts University. Tisch Library., 2022)
Keywords: Duchenne muscular dystrophy, Caregiver impact, Demographic, Quality of life, Stress, Behavioral, Cognitive, Resilience, COVID.; Springer Open.